Work-Life Balance and National Context in Attraction to Public Employment. Issue 4 (12th March 2019) - Moltz, Michael C.
ABSTRACT: What explains preferences for public employment versus private business employment. Much of the extant literature considers this topic within the context of single-nation studies and the work motives of those individuals already employed by government. This study contributes to the public-management literature with a cross-national examination of government employment preferences across 31 national samples using data from the International Social Survey Programme. Results indicate that a desire for more work-life balance is negatively associated with a preference for government employment and that measures of national economic health help explain the variation in preferences for government employment across nations.